Becoming Ottoman: converts, renegades and competing loyalties in the early modern and modern ages - Köse, Yavuz; Kučera, Petr; Völker, Tobias (I.B. Tauris, 2025)
"This book examines the role of Europeans who settled in the Ottoman Empire between the 16th and 19th centuries and assumed an "Ottoman identity", be it by way of conversion to Islam and assimilating to the host society or by becoming loyal servants or subjects of the Ottoman state, identifying themselves as Ottomans, but retaining their faith. Bringing together a variety of case studies that reflect a broad range of individual experiences in changing historical circumstances, the book provides a detailed study of the process of Ottomanization. The book draws upon a variety of archival and other sources such as juridical documents, travelogues, diaries and chronicles, including lesser-known examples, from early-modern Czech, Hungarian and Moldavian or Italian views of converts and conversion cases, to case studies of 19th century Germans, Hungarians and Austrians who switched loyalty. They show that this process depended on a range of factors, from conversion, to integration into the culture of the ruling elites, fluency in the language, affiliation through family ties or marriage, and, most importantly, social status and professional rank"--